Empowerment Pattern for Thalasemi Patients in Dr. Soetomo Hospital Surabaya (Study of the Association of Parents with Thalassemia Indonesia, Surabaya) - Saputra Adiwijaya; Dor Valda A Aritonang; Mustain Mashud (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Thalassemia is a hereditary disease that until now there is no effective treatment for healing, this disease is not contagious and generally attacks children with a variety of typical symptoms that can be detected since the age of a toddler (under five years). In the city of Surabaya there were 520 sufferers, this number was based on data from the administrators gathered in the organization of the POPTI (Association of Indonesian thalassemia Parents) in the city of Surabaya. There is a pattern of empowerment carried out by the management of POPTI in Surabaya to parents whose children suffer from thalassemia, as well as to adult patients. The thing to do is to conduct routine assistance at Dr. Soetomo Surabaya hospital every Tuesday and Wednesday. The purpose of this study is to describe and analyze the pattern of empowerment carried out by POPTI (Association of Parents with thalassemia Indonesia) in Surabaya in the treatment of thalassemia in Surabaya. This study used a qualitative method with a descriptive approach, with the primary data of the study obtained through in-depth interviews with 9 (nine) parents whose children suffered from thalassemia as key informants, the details of which consisted of 3 (three) POPTI administrators in Surabaya and 6 (six) members POPTI city of Surabaya. Based on the results of the analysis and discussion, the conclusions of the study are: 1) The joining of parents in the POPTI city of Surabaya provides many benefits in the care of their children who suffer from thalassemia in Dr. Soetomo Hospital Surabaya; 2) The form of empowerment patterns carried out by parents of elderly patients who are members of the POPTI container in Surabaya starts with routine mentoring which results in a shared value for parents; 3) There is a tiered learning pattern from patients who are considered senior to teach other patients in terms of understanding and ability to understand the flow of care services to thalassemia patients